The Equilibrium Ownership of an International Oligopoly - Henrik Horn; Lars Persson (The Research Institute of Industrial Economics (IUI), 1999)
Mergers and acquisitions (M&A) is the dominant form of Foreign Direct Investment (FDI), but has received but scarce attention in the theory literature on trade and investment. This paper highlights how the international pattern of ownership of productive assets may depend on features of trade and production costs. It suggests how high trade costs may be conductive to national ownership of assets, while international firms may arise at lower trade costs, contrary to what the 'tariff jumping' argument would suggest. It also shows how private and social incentives for M&A may differ for weak merger synergies, but converge when synergies are stronger.
Keywords: F23; L13; 330; International mergers; Endogenius market structure; Tariff jumping FDI; Internationale Unternehmenskooperation; Fusion; Auslandsinvestition; Oligopol; Wohlfahrtsanalyse; Theorie